HADIS BEROBAT DENGAN BENDA HARAM DALAM SUNAN ABU DAWUD METODE MUKHTALIF Al-HADIS SYAIKH SHALIH AL-USAIMIN - Abdul Haqqi; Ahmad Tamimi; Ahmad Daman Huri (Pusat Riset dan Inovasi Nasional, 2023)
Hadith is one of the pillars of Muslims in carrying out Islamic law. Besides that, hadith is also a sharp weapon for orientalists in bringing down Islam. One of the bases used by orientalists in overthrowing Islam is the hadiths that seem textually contradictory. Hadith that appear to be textually contradictory can cause misunderstandings for the general public if they do not examine them in depth. One example is the hadith narrated by Abū Dāwud which contradicts the permissibility and prohibition of using illicit objects in medicine. Therefore, researchers conducted research on the meaning and completion of the two hadiths. This type of research is qualitative in nature (library research) with descriptive presentation and analysis methods. This research also uses the book of Sunan Abū Dāwud and is assisted by other standard books, then it is analyzed by studying the Mukhtalif al-Ḥadīṡ method of Syaikh Shāliḥ al-Uṡaimin to resolve the two contradictory hadiths. The result of this study is that the two hadiths can be solved using the al-Jam'u method. Based on the compromise of the two hadiths, it is known that the use of illicit objects is permissible with certain considerations and conditions.